Examining Psychologists’ Competence and Cultural Adaptations in Therapy When Working with Latina/o Clients - (:unkn) unknown (My University, 2016)
The following multiple case study used semi-structured qualitative interviews and quantitative data to examine the multicultural competencies and cultural adaptations of four psychologists during a mock therapy session. This study consisted of three components: (1) Pre-Task, a semi-structured interview; (2) Task, each participant completing a mock therapy session with the same mock client and; (3) Post-Task, followed the client sessions and consisted of a semi-structured interview, a demographic questionnaire and two paper-pencil self-report measures. Immediately after each therapy session with the participants, the mock client completed two paper-pencil measures and a brief semi-structured interview about the participants. Three multicultural psychology experts with knowledge and clinical experience in multicultural competencies and Latina/o psychology observed and evaluated the task. Results of this study showed variability between rating of multicultural competency between the self-rating of the participants, the mock client and the expert observers. Broadly, three themes emerged from qualitative analysis of interviews with participants: (1) Explicit and Implicit Use of Multicultural Awareness, Knowledge, and Skills, (2) Self-Reflections on Cultural Identity and Values in the Therapeutic Relationship, and (3) Theory and Competencies. Findings from this study further clarified from the perspective of the psychologist, mock client and expert observer’s multicultural competencies and cultural adaptations.
Keywords: Latina/o Specific Competencies; Multicultural Competencies